Anteseden Loyalitas dan Keterlibatan Pelanggan terhadap Penggunaan Chatbot “MITA” Bank Mandiri - Azizah, Alfimalia Nurul; Hartono, Arif (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This study aims to evaluate the influence of trust on customer loyalty and engagement in the use of the “MITA” chatbot by Bank Mandiri trough WhatsApp Business. The analyze factors include privacy and security concerns, dispositional trust, technology fear, and ubiquity. Using a quantitative method with PLS-SEM analysis, data were collected trough an online survey of Bank Mandiri customers who have used the MITA chatbot. The findings reveal that privacy and security concerns, as well as technology fear, negatively affect trust, while dispositional trust and ubiquity have a positive impact. Furthermore, user trust in the chatbot plays a crucial role in enhancing customer loyalty and engagement with digital banking services.